AUTOLOGOUS PLATELET‐RICH PLASMA: A REVIEW OF SCIENTIFIC ARTICLES ON THE STUDY OF EFFICIENCY IN TREATMENT OF ANDROGENETIC ALOPECIA IN MEN AND WOMEN - Ovcharenko, Julia; Salenkova, Olena (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
This article is an analysis of scientific publications that reflect the experience of using autologous plateletrich plasma in patients with androgenic alopecia (AGA), a multifactorial genetically predisposed disease caused by the influence of exogenous or endogenous triggers responsible for the clinical manifestations of pathology. Attention to this topic is due to the significant prevalence of AGA, as well as unsatisfactory results in achieving a positive therapeutic effect. Positive results were obtained during the 12 clinical studies among the conducted ones, no positive dynamics were observed in the end of other 2 studies. It can be noted that different methods and parameters of centrifugation were used to perform these experiments: PRP used differ or PRP activators were not used at all, variations were observed in methods for evaluating the obtained results, the multiplicity of procedures and intervals between them, the procedure technique (using a mezoroller, anesthetics, injections, etc.). Studies with a negative result were characterized by the smallest number of procedures performed (1 or 2 procedures), and methods for evaluating the results cannot be called sufficiently reliable (a magnifying glass). It is obvious that the use of PRP has a positive effect on the state of AGA and can be used with approved methods of this disease treatment. However, the published results of only a small number of clinical trials on the effectiveness of PRP for hair growth cannot be considered objective. In addition, there is no published agreed protocol for the standard use of PRP, and the use of growth factors and stimulants in the expression of their genes still requires comparative evaluation with preparations approved for the treatment of hair. Thus, the method of PRP using can be considered as a method of treating AGA, however, it is necessary to continue research for further study and standardization of this technique.